Performance - and health-related benefits of youth resistance training - Chaabene, H.; Lesinski, M.; Behm, D. G.; Granacher, U. (Sport-Orthopädie - Sport-Traumatologie, 2020)
Summary There is ample evidence that youth resistance training (RT) is safe, joyful, and effective for different markers of performance (e.g., muscle strength, power, linear sprint speed) and health (e.g., injury prevention). Accordingly, the first aim of this narrative review is to present and discuss the relevance of muscle strength for youth physical development. The second purpose is to report evidence on the effectiveness of RT on muscular fitness (muscle strength, power, muscle endurance), on movement skill performance and injury prevention in youth. There is evidence that RT is effective in enhancing measures of muscle fitness in children and adolescents, irrespective of sex. Additionally, numerous studies indicate that RT has positive effects on fundamental movement skills (e.g., jumping, running, throwing) in youth regardless of age, maturity, training status, and sex. Further, irrespective of age, sex, and training status, regular exposure to RT (e.g., plyometric training) decreases the risk of sustaining injuries in youth. This implies that RT should be a meaningful element of youths` exercise programming. This has been acknowledged by global (e.g., World Health Organization) and national (e.g., National Strength and Conditioning Association) health- and performance-related organizations which is why they recommended to perform RT as an integral part of weekly exercise programs to promote muscular strength, fundamental movement skills, and to resist injuries in youth.